2017
DOI: 10.2174/1874282301711010044
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic Analysis of Worldwide Temperature Proxies for 2000 Years

Abstract: Abstract:The Sun as climate driver is repeatedly discussed in the literature but proofs are often weak. In order to elucidate the solar influence, we have used a large number of temperature proxies worldwide to construct a global temperature mean G7 over the last 2000 years. The Fourier spectrum of G7 shows the strongest components as ~1000-, ~460-, and ~190 -year periods whereas other cycles of the individual proxies are considerably weaker. The G7 temperature extrema coincide with the Roman, medieval, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
2
4
0
Order By: Relevance
“…Figure 1 shows an example of the SFA analysis for record 5 of Table 1 ; here, this analysis identifies significant oscillations with central periods of 187, 485, and 970 years. These are closely similar to periods 188, 463 and 1003 years found in [ 14 ] using Fourier analysis. The analogous results for other records are shown in the Supplementary material (Figures S4–S14) .…”
Section: Resultssupporting
confidence: 88%
“…Figure 1 shows an example of the SFA analysis for record 5 of Table 1 ; here, this analysis identifies significant oscillations with central periods of 187, 485, and 970 years. These are closely similar to periods 188, 463 and 1003 years found in [ 14 ] using Fourier analysis. The analogous results for other records are shown in the Supplementary material (Figures S4–S14) .…”
Section: Resultssupporting
confidence: 88%
“…These results are in good agreement with a study [18] reporting a harmonic analysis of worldwide temperature proxies for 2,000 years incorporating six previous global proxy temperature records. This showed the strongest components as sine waves with periodicities of ~1,000 years, ~460 years, and ~190 years, whereas other oscillations of the individual proxies are considerably weaker Another investigation [51] undertook wavelet analysis showing the dominant periodic variations of 1,130, 790-770, 560 and 390-360 years for Greenland ice core records extending over a period of 4,000 years.…”
Section: Decomposition Of Proxy Temperature Records Into Sets Of Component Sine Wavessupporting
confidence: 91%
“…Identification of continuing oscillatory patterns can potentially be valuable in forecasting temperatures. A number of studies have found evidence for oscillations in proxy records at millennial, centennial and decadal time scales by applying spectral analysis [18][19][20]. It has been suggested that some proxy records may not include low frequency oscillations because certain types of proxy (particularly tree rings) do not capture this compared to others proxies such as ice cores.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations